The development of model improving health literacy of rational drug use for sepsis prevention in community, Uthai Thani Province - Munsoom, Parawee; Ruenruay, Siriluk (Journal of Medical and Public Health Region 4, 2026)
Sepsis is a substantial health burden with a high mortality rate. This research and development study aimed to create a literacy model in rational drug use to prevent sepsis. The study also examines the effects of implementing this literacy model in pilot areas, specifically at Rong Ta Tee Sub-district Health Promoting Hospital in Lan Sak District and Thung Pho Sub-district Health Promoting Hospital in Nong Chang District, Uthai Thani Province. We collected data from meeting records, observations, monitoring, and evaluations of activities. We conducted the assessment using literacy evaluation tools, and data were analyzed using descriptive statistics. We performed a comparison of pre-and post-intervention results using a paired-sample t-test. The results revealed that, after six months of implementing the literacy model in the pilot areas, 374 participants selected through systematic random sampling showed a significant improvement in health literacy (p<0.001; pre-test 61.12±24.79, post-test 66.61±26.88). Consequently, applying the literacy model for rational drug use in preventing sepsis at the community level in Uthai Thani Province effectively enhanced health literacy. It also improved individuals’ skills in accessing, understanding, critically analyzing, and making informed decisions regarding rational drug use. Furthermore, participants communicated this knowledge to their families and communities, contributing to the prevention of sepsis, which remains a critical health concern in Uthai Thani Province.